Role of the pair potential for the saturation of generalized Pauli constraints - Legeza, O; Schilling, C (American Physical Society, 2018)
The dependence of the (quasi-)saturation of the generalized Pauli constraints on the pair potential is studied for ground states of few-fermion systems. For this, we consider spinless fermions in one dimension which are harmonically confined and interact by pair potentials of the form |xi−xj|^s with −1≤s≤5. Using the Density Matrix Renormalization Group-approach and large orbital basis sets ensures the convergence on more than ten digits of both the variational energy and the natural occupation numbers. Our results confirm that the conflict between energy minimization and fermionic exchange symmetry results in a quasi-saturation of the generalized Pauli constraints (quasipinning), implying structural simplifications of the fermionic ground state. However, a self-consistent perturbation theory reveals that most of that relevance has to be assigned to Pauli's original exclusion principle, except for the harmonic case, i.e., s=2. This emphasizes the unique nature of the strong, non-trivial quasipinning found recently for the Harmonium model.